Kallummakkaya: A feasibility study on jarred mussels - Biolangco, Vianca Denise C. Bocacao, ezekiela P. Cabanganan, Pricess Nove P. Catuday, Marielle Kaye Athena M. De Dios, Janice Dane M.Farinas, Marc Jade A. Ilao, Jhemil anne a. Mabale, Rikki Mae D. Relucio, Ash;ey Janine S. Reyes, Angelo 4 0 16; 5
ABSTRACT: Seafood has always been a significant part of the market, and it has always been a staple in the diets of Filipino families. Because of the archipelagic structure of the nation that makes farming a significant source of revenue, fishing has always been an important occupation in the Philippines. Mussels, which are commonly referred to as tahong in the Philippines, are grown almost exclusively in the Navotas Fish Port Complex, which is called the capital fish port in the Philippines where Kallummakkaya's activities will be carried out serving as a competitive advantage. Dishes made with mussels have a special place in every Filipino's heart. Therefore, the firm reimagines and produces sufficient jarred mussels while following a stringent commitment to sustainable aquaculture and ensuring the customer's satisfaction level. To ensure that farmers in today's contemporary society can regain their role in the community, the primary objective of the firm is to offer innovative solutions to this problem. Jarred tahong will be produced in several distinct flavors to accommodate a wide range of consumers' preferences while preserving the product's pleasing look. As our business expands, we want to meet the needs of our customers by offering a wider selection of seafood in response to their requests. We will focus on the benefits that our products can provide and will make every effort to improve the overal quality of the experience of consumers by producing high-quality goods. Kallummakkaya aims to living up to the expectations of its stakeholders by conducting business in a manner that is methodical, competitive, sustainable and profitable. In addition, the enterprise has committed itself to environmentally conscious and socially engaged tasks that promote responsible care of the natural world. The company will guarantee that the food production process complies with the food safety regulatory system and sanitation safety standards by ensuring that waste is disposed of properly, that food is stored at appropriate temperatures, that safe water and raw materials are used, that the workplace is kept clean, and that other sanitation measures are implemented.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2